Effect of Calcination Time on the Catalytic Activity of Ni/γ-Al2O3 Cordierite Monolith for Dry Reforming of Biogas. (3rd February 2021) - Chava, Ramakrishna; Purbia, Devendra; Roy, Banasri; Janardhanan, Vinod M.; Bahurudeen, A.; Appari, Srinivas
Abstract: Ni/γ-Al2 O3 wash coated cordierite monolith catalysts are calcined in air at 800 °C for 4, 10, and 20 h in order to study the effect of calcination time on the activity of the catalysts for dry reforming of model biogas. Catalytic activity studies are performed at 800 °C with three different CH4 /CO2 ratios of 1.0, 1.5, and 2.0. The catalyst calcined for the longest time (C-20) displays higher stability and activity in terms of CH4 and CO2 conversion compared to those calcined for 4 h (C-4) and 10 h (C-10). XRD data and TPR analysis detect the maximum amount of NiAl2 O4 /MgAl2 O4 phases and strongest metal-support interaction, respectively, for the C-20 sample. FESEM reveals the particle size of the calcined and reduced C-20 sample to be smaller than that of the C-4 and C-10 samples. Whereas, H2 pulse-chemisorption characterization demonstrates the highest metal surface area, metal dispersion, and smallest Ni particle size for the C-20 catalyst. While, no carbon deposition on any catalyst occurs for the CH4 /CO2 ratio of one, lowest amount of carbon nanotubes is formed on the C-20 sample for the CH4 /CO2 ratio of 1.5 and 2.0, as observe by DTA-TGA. EDX reveals concentration variation of Mg and Si from the cordierite monolith wall along the thickness of the coating for all the samples. In addition, the maximum amount of these elements is observed for the calcined C-20 catalyst coating. These implies that the diffusion of Mg and Si from the cordierite monolith to the catalyst coating during calcination contribute significantly in controlling the physicochemical properties of the catalysts. As a result, the higher stability and activity of the C-20 could be attributed to the formation of higher amount of the Ni– Mg- alumina spinel complex in the catalyst coating during longer calcination time, which leads to the improved metal-support interaction and higher nickel dispersion over monolith. Highlights: Ni/γ-Al2 O3 coated monoliths are calcined for 4, 10, & 20 h. Called C-4, C-10 & C-20. Effect of calcination time on activity of the catalysts for DR of biogas is studied. C-20 shows the highest CH4 and CO2 conversions for the CH4 /CO2 feed ratios ≥1. C-20 demonstrates the smallest Ni particle size and highest metal dispersion. Diffusion of Mg & Si to the catalyst coating might be responsible for better activity.